Restructuring Agricultural Research, Extension and Education in Nepal’s Federal System - Timsina, K.P.; Ghimire, Y.N.; Gauchan, D.; Sanjel, P.K.; Padhyoti, Y.; Bista, H.B. (Nepalese Horticulture, 2018)
Abstract available with the full text.